Monitoring the impacts of weather radar data quality control for quantitative application at the continental scale. (22nd July 2020) - Michelson, Daniel; Hansen, Bjarne; Jacques, Dominik; Lemay, François; Rodriguez, Peter
Abstract: As part of a suite of quality control methods applied to Canadian and American weather radar data before their assimilation into a numerical weather prediction model, the combination of thresholded depolarization ratio and a speckle filter was applied to American data with the purpose of identifying and removing non‐precipitation echoes. This polarimetric quality control replaces a set of image‐analysis‐based methods used in a previous study and based on reflectivity information only. The old and new quality‐controlled results were objectively assessed using meteorological aerodrome report (METAR)‐based precipitation occurrence observations and a set of five common contingency table skill scores with all available Next Generation Weather Radar (NEXRAD) Level II data from the contiguous United States for August 2016. The new quality control yields consistently improved skill scores, indicating higher quality radar data for downstream application. The process whereby the radar data are quality controlled and assessed comprises a framework with the ability to monitor the impacts of quality control to radar data quality over time. In turn, this allows for the introduction of changes to data acquisition and processing with the ability to monitor the impacts on data quality: a scientific evidence‐based quality assurance process as part of change management. Abstract : Weather radar data from across North America were quality controlled using a simple method based on depolarization ratio. Precipitation occurrence observations from METARs and five common statistical skill scores were used to assess the new quality control objectively compared with previous results from legacy image‐analysis methods and reflectivity information only. The new polarimetric method yields significantly improved data quality, and the assessment process gives a monitoring framework for scientific evidence‐based quality assurance as part of change management.